The Use of the Think-Pair-Share Strategy to Improve Writing Skills at the State Islamic Junior High School of Batu - Rahmah Fadhilah Agustina; Muhammad Syihabul Ihsan Al Haqiqy (An-Nahdloh: Journal of Education and Islamic Studies, 2025)
The focus of learning has been primarily on memorization of mufrodat, leaving students with little opportunity for writing practice. The Think Pair Share strategy encourages all students to actively participate in writing activities, which not only strengthens memorization but also encourages students to actively use vocabulary in their writing. The purpose of this research is to measure the effectiveness of the Think Pair Share strategy in improving writing skills at Madrasah Tsanawiyah Negeri Batu. This research uses a quantitative method with a Quasi-Experimental design and a Nonequivalent Control Group Design. The research sample consisted of 64 eighth-grade students from MTsN Kota Batu, with 32 students in the experimental group and 32 students in the control group. Data collection was conducted using observation, interviews, and tests. Data analysis techniques used normality tests, homogeneity tests, followed by hypothesis testing using the Independent Sample T-Test. The research results showed that the use of the Think Pair Share strategy was effective in improving the writing skills of eighth-grade students at MTsN Kota Batu. Based on hypothesis testing using the independent t-test, a significance value of 0.000 was obtained, which is less than 0.05. Therefore, the null hypothesis (H0) was rejected, and the alternative hypothesis (Ha) was accepted. Including: increasing students' thinking ability, providing thinking time to improve the quality of students' responses, making students more active in thinking about concepts in the subject matter, students having a better understanding of the concepts of the lesson topics during discussions, students being able to learn from other students, and every student in the group having the opportunity to share or convey their ideas. Keywords: Strategy, Think Pair Share, Writing Skills